Método propuesto para la traslación de la curva I-V de un módulo fotovoltaico medida bajo condiciones reales de operación a diversas condiciones de funcionamiento - Nakama Martínez Víctor Luis (2017)
In this research a mathematical method for the translation of the I-V curve of a photo- voltaic module measured under actual operating conditions to various operating conditions is described. This work began in turn to the development of a proprietary method to extracting parame- ters of the I-V curve. A study of the behavior of these parameters with respect to variation of the incident radiation on the photovoltaic module and the temperature of this is then made, in order to predict the value of each of these parameters under any desired condition of irradiance and temperature to thus be able to draw the new I-V curve that reflecting the electrical performance of the photovoltaic module under these new conditions of irradiance and temperature. For this work, calibrated photovoltaic module has been used which allows to know its electrical performance under standard conditions of measurement, this allows us to perform the translation of the I-V curve to the mentioned conditions and to analyze the reliability of the results.